The psychological background of masticatory system parafunctions - Pawlaczyk-Kamieńska, Tamara (Journal of Stomatology, 2018)
In recent years there has been a growth noted in the number of people suffering the effects of the masticatory organ motoric disorders which arise as a consequence of parafunctions. Some of them accompany mental disorders where practising parafunctions may ease anxiety and stress. Unfortunately, these parafunctions may produce injuries in the mouth. Moreover, they strain the motor system of the masticatory organ unevenly. This may lead to formation and fixation of a deviated model of function and, with time, to morphological and functional changes. Identification and elimination of a causative factor is essential in undertaking proper and effective treatment of these disorders. Moreover, it is necessary to promote parafunctions prophylaxis and to provide comprehensive, team-based treatment. It seems purposeful to implement comprehensive therapy at an early stage of the problem as a part of psychologic treatment, too. It should aim at eliminating harmful habits resulting in secondary somatic complications. The paper presents current views on etiology of masticatory organ parafunctions.